TOTAL ERITROSIT DAN LEUKOSIT BROILER BETINA SETELAH PEMBERIAN JINTAN HITAM (Nigella sativa) SEBAGAI IMUNOMODULATOR DALAM AIR MINUM - Noven Hariyani; Siswanto Siswanto; Sri Suharyati; Purnama Edy Santosa (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2020)
The study aimed to determine the effects of black cumin extract (Nigella sativa) and determine the optimal dose of black cumin extract (Nigella sativa) on total erythrocytes and leukocytes broilers. This research was conducted from December 2019 to January 2020 at the Integrated Field Laboratory Unit of the Faculty of Agriculture, University of Lampung. The research data were analyzed at Pramitra Biolab Indonesia Laboratory, Bandar Lampung. The research material was 60 female broilers (strain Cobb CP 707). This study used a Completely Randomized Design with 4 treatments and 3 replications. The treatments in this study were drinking water without Nigella sativa (P0), drinking water with Nigella sativa 36 mg/kg BW/day (P1), drinking water with Nigella sativa 72 mg/kg BW/day (P2) and drinking water with Nigella sativa 144 mg/kg BW/day (P3). Data obtained from observations were arranged in the form of simple tabulations and displayed in the form of histograms for descriptive analysis. Research showed that female broilers given black cumin (Nigella sativa) in their drinking water affected on the total erythrocytes which was in the normal range and the total leukocytes which were above the normal range in all treatment. The best dose of black cumin (Nigella sativa) in drinking water for each parameters was 144 mg/kg BW/day for total erythrocytes and 72 mg/kg BW/day for total leukocytes. Keywords: Black cumin (Nigella sativa), Erythrocytes, Female broilers, Immunomodulator , Leukocytes